2009
DOI: 10.3758/pbr.16.4.705
|View full text |Cite
|
Sign up to set email alerts
|

The bilingual advantage in novel word learning

Abstract: The present study examined whether bilingualism facilitates acquisition of novel words in adults with different language histories. Word-learning performance was tested in monolingual English speakers, early English-Spanish bilinguals, and early English-Mandarin bilinguals. Novel words were phonologically unfamiliar to all participants, and they were acquired in association with their English translations. At testing, both bilingual groups outperformed the monolingual group. These findings indicate that biling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
258
14
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 225 publications
(308 citation statements)
references
References 20 publications
31
258
14
5
Order By: Relevance
“…Here, we discover that language learning, like more explicit music instruction, also impacts subcortical sound processing. This enhanced neural representation of the auditory signal may facilitate learning a new language, a skill in which bilinguals outperform monolinguals (46). Indeed, musicians, who show neural enhancements similar to bilinguals, also appear to be better able to detect acoustic cues in foreign speech relative to nonmusicians (32,45,47).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we discover that language learning, like more explicit music instruction, also impacts subcortical sound processing. This enhanced neural representation of the auditory signal may facilitate learning a new language, a skill in which bilinguals outperform monolinguals (46). Indeed, musicians, who show neural enhancements similar to bilinguals, also appear to be better able to detect acoustic cues in foreign speech relative to nonmusicians (32,45,47).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, more recent studies reported no consistent evidence for a major role of language combination for bilingual benefits (e.g., Coderre & van Heuven, 2014;Kaushanskaya & Marian, 2009;Kirk, et al, 2014).…”
Section: Limitationsmentioning
confidence: 99%
“…We selected 8 pairs, which is typical of visual-verbal PAL studies (see Mayringer & Wimmer, 2000;Messbauer, & De Jong, 2003;Papagno & Vallar, 1995;Warmington & Hitch, 2014). Unlike previous studies which focused on immediate learning (e.g., Kaushanskaya & Marian, 2009a;Papagno & Vallar, 1995) we were additionally interested in assessing language group differences regarding the integrity of the newly learned items over the long-term. Thus, participants' learning was assessed both immediately and one day later.…”
Section: Overview Of Present Studymentioning
confidence: 99%